Pemikiran Kontemporer dalam Studi Islam: Nurcholis Madjid dan Fouad Zakaria - Sabani, Rizki Fathul Anwar (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This article explores the thoughts of two contemporary Muslim thinkers, Nurcholis Madjid from Indonesia and Fouad Zakaria from Egypt, regarding secularism as an ongoing issue within modern Islamic discourse. The main problem addressed is how both thinkers conceptualize and interpret secularism in the context of their respective religious and national frameworks. This study aims to compare Madjid’s and Zakaria’s intellectual approaches in interpreting the relationship between religion and the state. The research employs a qualitative method using library research, with primary and secondary data analyzed through descriptive-critical interpretation. The findings indicate that Madjid promotes Islamic reform in Indonesia by positioning secularism contextually, without fully separating religion and the state. Zakaria, on the other hand, develops secularist ideas in the Egyptian context to preserve religious rationality amid political and social complexity. Both thinkers challenge the narrowed interpretation of secularism, often misunderstood by Islamist groups as a form of apostasy Abstrak: Artikel ini membahas pemikiran dua tokoh Muslim kontemporer, Nurcholis Madjid dari Indonesia dan Fouad Zakaria dari Mesir, dalam memandang sekularisme sebagai isu yang terus berkembang dalam diskursus keislaman modern. Permasalahan utama dalam penelitian ini adalah bagaimana kedua tokoh tersebut memahami dan memaknai konsep sekularisme dalam konteks keislaman dan kebangsaan yang berbeda. Penelitian ini bertujuan untuk membandingkan pendekatan intelektual Madjid dan Zakaria dalam menafsirkan hubungan antara agama dan negara. Metode yang digunakan adalah kualitatif dengan pendekatan studi pustaka (library research), menggunakan data primer dan sekunder yang dianalisis secara deskriptif-kritis. Temuan penelitian menunjukkan bahwa Madjid berupaya menawarkan pembaruan pemikiran Islam di Indonesia dengan mendudukkan sekularisme secara kontekstual, tanpa memisahkan sepenuhnya antara agama dan negara. Sementara itu, Zakaria mengembangkan gagasan sekularisme dalam konteks Mesir sebagai upaya mempertahankan rasionalitas agama di tengah kompleksitas politik dan sosial. Keduanya sama-sama mengkritisi penyempitan makna sekularisme yang cenderung disalahpahami oleh kelompok Islamis sebagai bentuk kekufuran. Kata kunci: Nurcholis Madjid, Fouad Zakaria, sekularisme